2016
DOI: 10.1021/acs.biochem.5b01169
|View full text |Cite|
|
Sign up to set email alerts
|

Contributions of Coulombic and Hofmeister Effects to the Osmotic Activation of Escherichia coli Transporter ProP

Abstract: Osmosensing transporters mediate osmolyte accumulation to forestall cellular dehydration as the extracellular osmolality increases. ProP is a bacterial osmolyte-H+ symporter, a major facilitator superfamily member, and a paradigm for osmosensing. ProP activity is a sigmoid function of the osmolality. It is determined by the osmolality, not the magnitude or direction of the osmotic shift, in cells and salt-loaded proteoliposomes. The activation threshold varies directly with the proportion of anionic phospholip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(51 citation statements)
references
References 54 publications
4
47
0
Order By: Relevance
“…Coulombic salt effects on protein stability are oen predicted to scale with the Debye-Huckel limiting law, i.e., linearly depend on the square root of the solvent ionic strength. [72][73][74][75][76] It has however been shown that there is no real justication for this assumption 72 and a more thorough analysis of salt-induced coulombic effects on protein folding free energy predicts that for the monovalent salts in this study they following functional form: 9,40 Salt-induced Coulomb effects ¼ DDG unfolding…”
Section: Thermodynamic Analysismentioning
confidence: 83%
See 2 more Smart Citations
“…Coulombic salt effects on protein stability are oen predicted to scale with the Debye-Huckel limiting law, i.e., linearly depend on the square root of the solvent ionic strength. [72][73][74][75][76] It has however been shown that there is no real justication for this assumption 72 and a more thorough analysis of salt-induced coulombic effects on protein folding free energy predicts that for the monovalent salts in this study they following functional form: 9,40 Salt-induced Coulomb effects ¼ DDG unfolding…”
Section: Thermodynamic Analysismentioning
confidence: 83%
“…Most systematic analyses of salt effects on proteins postulate that salt addition inuences the stability of proteins through nonspecic Coulomb and ion-specic Hofmeister effects. 9,40,62 The formalism of Record et al, 9,33,[36][37][38][39][40]62,63 quanties Hofmeister effects on the protein folding process by "m-values", the derivative of the free energy of unfolding with respect to salt concentration: ‡…”
Section: Thermodynamic Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli cannot synthesize ectoine but it can import it via the osmotically inducible ProP and ProU osmostress protectant uptake systems [ 60 , 61 ]. ProP is a proton/solute symporter and a member of the major facilitator (MFS) superfamily [ 62 ], whereas ProU belongs to the multi-component ABC-type of transport systems [ 63 , 64 ]. Ectoine is likely to permeate across the E. coli outer membrane by diffusion through the general porins OmpC and OmpF (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For energetic reasons (18), the import of preformed compatible solutes is preferred over their synthesis, and consequently, uptake systems for these stress-relieving compounds are frequently a cornerstone of the cellular osmostress response systems of bacteria (1, 4-6, 19, 20). A considerable number of compatible solute transporters have been identified in bacteria that belong to different transporter families, as follows: binding-protein-dependent ATP-binding cassette (ABC) systems (21) (e.g., the ProU, OpuA, OpuB, OpuC, BusA, OsmU, OusA, and Prb transporters [22][23][24][25][26][27][28][29][30]), members of the major facilitator superfamily (MFS) (31) (e.g., the ProP and OusA transporters [32][33][34]), members of the betaine-choline-carnitine transport (BCCT) systems (35) (e.g., the OpuD, BetP, BetS, EctT, EctP, EctM, and BetM transporters [33,[36][37][38][39]), members of the sodium-solute-symporter (SSS) family (40) (e.g., OpuE [41]), and members of the tripartite ATP-independent periplasmic transporters (TRAP-T) (42) (e.g., the TeaABC system [43]). In addition to the typical osmotic induction of the transcription of their structural genes (1,(3)(4)(5)(44)(45)(46), the activities of compatible solute transporters are also frequently enhanced by osmotic stress (6,19,20,32,35,47,48), thereby providing bacterial cells with increased uptake capacity for stress-relieving compounds both under acute and sustained high-osmolarity conditions.…”
mentioning
confidence: 99%